THE INFLUENCE OF TOURISM IMPACTS AND DESTINATION SOCIAL RESPONSIBILITY ON SUPPORT FOR TOURISM DEVELOPMENT: A CONCEPTUAL MODEL - Mohammed Alawi Al-sakkaf; Zurina Mohaidin; Yulita Hanum P. Iskan; Mohsen Ali Murshid; Saleh Amarneh (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Support for tourism development is a novel idea that is regarded as one of the most current trends in tourism literature; it is still a developing research subject in various regions of the world. Saudi Arabia is an appropriate emerging economy to explore tourism development. This study contributes to the literature by investigating the support for tourism development and its determinants in Saudi Arabia after the Kingdom opened its doors to tourism in late 2018. By combining the social exchange theory and stakeholder theory, this article proposes a conceptual model to explore the moderating effect of destination social responsibility on the relationship between tourism impacts and support for tourism development. The study proposes distributing a self-administered questionnaire to the respondent residents in order to acquire data on support for tourist development and other variables. The proposed conceptual model could be very useful; it can help tourism development organizations adopt tourism planning and sustainable tourism policies, destination management and social responsibility policies, or develop strategies and policies for more sustainable tourism, as well as create benefits for residents.